Intersection of labour and employment market in private further and higher education colleges in the United Kingdom - Luva, Rumana Huq; Jafor, Rakib Ullah; Uddin, Mohammad Jasim *; Tehseen, Shehnaz * (Academy of entrepreneurship, 2018)
While past literature identified that the unskilled workers tend to accept nonstandard works, the literature has not explained adequately the reasons for accepting nonstandard work by highly skilled academics. This study addresses this literature gap by examining various reasons for accepting non-standard work by academics in private further and higher education colleges in the United Kingdom. Based on self-determination motivation theory, the study categorizes different reasons according to push factors and pull factors where push factors are the controlled choices and pull factors are autonomous choices. A mixed methodology is employed in this study. The quantitative data are utilized to draw the trends and patterns of nonstandard work in this context, where the qualitative data are used to give an in-depth discussion about the context. Influences of both push and pull factor have been identified as a reason for accepting non-standard contract. However, the links between push factors are stronger than pull factors. We argued that when the push factors become powerful, the pull choice intersects with push factor, and in that situation the pull factors become less important to employees. We also argued that due to strong presence of push factor, the academics in this sector have less control over different aspects of job including wages, training, employment benefits, career progression, and job security.